2020
DOI: 10.1101/2020.02.17.20023747
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The reproductive number R0 of COVID-19 based on estimate of a statistical time delay dynamical system

Abstract: In this paper, we estimate the reproductive number R 0 of COVID-19 based on Wallinga and Lipsitch framework [11] and a novel statistical time delay dynamic system. We use the observed data reported in CCDC's paper to estimate distribution of the generation interval of the infection and apply the simulation results from the time delay dynamic system as well as released data from CCDC to fit the growth rate. The conclusion is: Based our Fudan-CCDC model, the growth rate r of COVID-19 is almost in [0.30, 0.32] wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 11 publications
0
42
0
1
Order By: Relevance
“…Recently, many researchers devoted to more details about the analysis of the spread of epidemic. 14,15 Some paralleled results have shown that the reproductive number R0 estimated of COVID-19 is bigger than that of SARS based on different models. [16][17][18] With the limited number of data points and the complexity of the real situation, a straightforward model is expected to work better (see Discussion).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many researchers devoted to more details about the analysis of the spread of epidemic. 14,15 Some paralleled results have shown that the reproductive number R0 estimated of COVID-19 is bigger than that of SARS based on different models. [16][17][18] With the limited number of data points and the complexity of the real situation, a straightforward model is expected to work better (see Discussion).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been performed that investigated the kinetics of coronavirus spread through human populations. The pattern of virus spread was found to be approximately exponential, at least during the early stages of virus spread [6,7], and importantly, the basic reproductive ratio of the virus has been estimated [8,9,10,11]. The implementation of social distancing measures are expected to have a significant impact on the virus spread kinetics [5], which has been observed in some Asian countries, such as China [12].…”
Section: Introductionmentioning
confidence: 99%
“…We introduce our model by adding a source term on the discrete version of the FUDAN-CCDC model that we proposed recently in [26]: for t > t 0 ,…”
Section: Modelmentioning
confidence: 99%
“…REMARK 1. Comparing with the FUDAN-CCDC model in [26], the source term I s (t) is introduced here, which is important since we think that the imported infected people in Singapore are from China or other counties. We recently found that the data could be fitted well only when the imported cases were carefully considered, and moreover the final infected numbers would be very different.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation